Small but stylish: pushing innovation ambidexterity in international Small and Medium Enterprises / Faizah Mashahad and Noor Hazlina Ahmad - Mashahad, Faizah; Ahmad, Noor Hazlina (Faculty of Business and Management UiTM Shah Alam, 2020)
Small and Medium Enterprises (SME) have been viewed as remarkable drivers for economic development. In comparison to big business entities, SME are highly flexible revealing better adaptability to changes in the market, making SME designers in innovative enterprises. With the opening of national boundaries, globalization brings more opportunities for SME to multiply its contribution to the growth and well-being of the country. Innovation capability is an essential element for cross-border transaction. International transaction has magnified SME investment in innovation capability to further improve business competitiveness and performance. The trick in dealing with multiple backgrounds customers resides in the SME capability to exploit its existing innovation and simultaneously explore new sphere of innovation. Observed as innovation ambidexterity, the capability permits SMEs to response dynamically and to combat increased uncertainties in the global market. Due to its premise that promotes adoptability and adaptability, it is rather important to identify antecedent of innovation ambidexterity. Since international entrepreneurial orientation serves as a fundamental drive for entrepreneurship activity in foreign countries, international entrepreneurial orientation that is viewed as a multiple dimension construct, is conceptually articulated as a significant predecessor of innovation ambidexterity in international SMEs in Malaysia.